2018
DOI: 10.3390/molecules23102482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Highly Detectable Pesticides Sprayed in Brassica napus L.: Degradation Behavior and Risk Assessment for Honeybees

Abstract: Honeybees are major pollinators of agricultural crops and many other plants in natural ecosystems alike. In recent years, managed honeybee colonies have decreased rapidly. The application of pesticides is hypothesized to be an important route leading to colony loss. Herein, a quick, easy, cheap, effective, rugged, and safe (QuEChERS) method was used to determine eight highly detectable pesticides (carbendazim, prochloraz, pyrimethanil, fenpropathrin, chlorpyrifos, imidacloprid, thiamethoxam, and acetamiprid) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Because bees were mainly exposed to sulfoxaflor by pollen and nectar when sulfoxaflor was applied via drip irrigation [44]. Firstly, we assessed the contact exposure of sulfoxaflor on honey bees by the flower hazard quotient (FHQ do ) [29], and the results showed that all FHQ do values were lower than 0.1, indicating that sulfoxaflor residues in pollen and nectar were safe to honey bees ( Table 4; Table 5) [29]. Honey bees generally have different types, such as worker larvae, nurses, and forager.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because bees were mainly exposed to sulfoxaflor by pollen and nectar when sulfoxaflor was applied via drip irrigation [44]. Firstly, we assessed the contact exposure of sulfoxaflor on honey bees by the flower hazard quotient (FHQ do ) [29], and the results showed that all FHQ do values were lower than 0.1, indicating that sulfoxaflor residues in pollen and nectar were safe to honey bees ( Table 4; Table 5) [29]. Honey bees generally have different types, such as worker larvae, nurses, and forager.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the risk of sulfoxaflor posed to A. mellifera, the risk assessment was estimated according to the flower hazard quotient (FHQ do ) value [29]. The FHQ do value was calculated from the predicted exposure concentration (PEC) in pollen and nectar multiplied by the maximum contact level (MCL)] and the acute contact LD 50 for adult bees.…”
Section: Risk Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The Special Issue had satisfactory feedback from researchers, with contributions having cross-field character and being of interest for different industrial, pharmaceutical, chemical, and biological fields [7][8][9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%